Information and Educational Space of an Economic University under the Digitalization - O. V. Gulina (Цифровая трансформация, 2021)
The paper summarizes the ideas about the educational information space, formulates its features for an economic university under the digital transformation of the economy, presents the expected positive effects and prospects for the creation and development of information and educational space based on information, communication and digital technologies, as well as possible risks and threats of digitalization for participants in the educational process.